UPAYA PENGENTASAN KEMISKINAN PADA PETANI MENGGUNAKAN MODEL TINDAKAN KOLEKTIF KELEMBAGAAN PERTANIAN - Satriawan, Bondan; Oktavianti, Henny (Universitas Muhammdaiyah Surakarta, 2012)
The objective of this study is to find way to reduce poverty rate of farmer by looking for the most suitable farm institutions that could be applied nationally. By doing so, this study analyzes, first, poverty condition of farmer through social-cultural approach in order to find the root causes of the farmer poverty. Secondly, this study will analyze current farm institutions. Finally, this study will synthesize the findings and proceed with alternative policies that are based on collective actions to overcome the poverty problem for the farmer. ZOPP (Zielorientierte Projektplanung-Objective Oriented Project Planning) and collective action model are used as the main method of analyze. This study finds that there are eleven root causes of farmer poverty. Furthermore, this study suggest the existence of: market creation, activating and assisting KUT (Farmer Business Union) as well as Gapoktan (Farmer Club), and providing a pilot field for farming for every village.